Tubulin Tail Sequences and Post-translational Modifications Regulate Closure of Mitochondrial Voltage-dependent Anion Channel (VDAC) - Sheldon, Kely L. (J Biol Chem, 2015)
It was previously shown that tubulin dimer interaction with the mitochondrial outer membrane protein voltage-dependent anion channel (VDAC) blocks traffic through the channel and reduces oxidative metabolism and that this requires the unstructured anionic C-terminal tail peptides found on both α- and β-tubulin subunits. It was unclear whether the α- and β-tubulin tails contribute equally to VDAC blockade and what effects might be due to sequence variations in these tail peptides or to tubulin post-translational modifications, which mostly occur on the tails. The nature of the contribution of the tubulin body beyond acting as an anchor for the tails had not been clarified either. Here we present peptide-protein chimeras to address these questions. These constructs allow us to easily combine a tail peptide with different proteins or combine different tail peptides with a particular protein. The results show that a single tail grafted to an inert protein is sufficient to produce channel closure similar to that observed with tubulin. We show that the β-tail is more than an order of magnitude more potent than the α-tail and that the lower α-tail activity is largely due to the presence of a terminal tyrosine. Detyrosination activates the α-tail, and activation is reversed by the removal of the glutamic acid penultimate to the tyrosine. Nitration of tyrosine reverses the tyrosine inhibition of binding and even induces prolonged VDAC closures. Our results demonstrate that small changes in sequence or post-translational modification of the unstructured tails of tubulin result in substantial changes in VDAC closure.